Habermas and Rawls : disputing the political - Finlayson, James Gordon; Freyenhagen, Fabian (New York : Routledge, 2011)
Habermas and Rawls are two heavyweights of social and political philosophy, and they are undoubtedly the two most written about (and widely read) authors in this field. However, there has not been much informed and interesting work on the points of intersection between their projects, partly because their work comes from different traditions-roughly the European tradition of social and political theory and the Anglo-American analytic tradition of political philosophy. In this volume, contributors re-examine the Habermas-Rawls dispute with an eye toward the ways in which the dispute can cast.
Introduction : the Habermas Rawls dispute : analysis and re-evaluation / James Gordon Finlayson and Fabian Freyenhagen -- Reconciliation through the public reason : remarks on John Rawls' political liberalism / Jürgen Habermas -- Political liberalism : reply to Habermas / John Rawls -- "Reasonable" versus "true", or, The morality of world views / Jürgen Habermas -- Justice : transcendental not metaphysical / Joseph Heath -- The justice of justification / Anthony Simon Laden -- The justification of justice : Rawls and Habermas in dialogue / Rainer Forst -- Procedure in substance and substance in procedure : reframing the Habermas-Rawls debate / James Gledhill -- Habermas, Rawls, and moral impartiality / Christopher McMahon -- Rawls and Habermas on the place of religion in the political domain / Catherine Audard -- Two models of human rights : extending the Rawls-Habermas debate / Jeffrey Flynn -- Beyond overlapping consensus : Rawls and Habermas on the limits of cosmopolitanism / James Bohman -- Reply to my critics / Jürgen Habermas.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Habermas, Jürgen.; Rawls, John, -- 1921-2002.; Habermas, Jürgen; Rawls, John, -- 1921-2002; Political science -- Philosophy; POLITICAL SCIENCE -- History & Theory; Political science -- Philosophy; Electronic book